FAMILY PERISCELIDIDAE - Rung, Alessandra (Zootaxa, 2016)
This catalog summarizes information on the three species of Periscelididae known to occur in Colombia. One species belongs to the subfamily Periscelidinae, and two to the Stenomicrinae. This catalog includes no new record for Colombia.